2018
DOI: 10.1158/1055-9965.epi-17-0378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time to Diagnostic Testing for Breast, Cervical, and Colorectal Cancer Screening Abnormalities on Screening Efficacy: A Modeling Study

Abstract: Patients who receive an abnormal cancer screening result require follow-up for diagnostic testing, but the time to follow-up varies across patients and practices. We used a simulation study to estimate the change in lifetime screening benefits when time to follow-up for breast, cervical, and colorectal cancers was increased. Estimates were based on four independently developed microsimulation models that each simulated the life course of adults eligible for breast (women ages 50-74 years), cervical (women ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 29 publications
(36 reference statements)
2
62
0
Order By: Relevance
“…The PROSPR multimodel study used 2 separate CRC modeling strategies side by side. That study reported an RR from 1.01 to 1.02 for lifetime disease risk at 3 months (compared with immediate diagnosis), an RR of 1.05 at 12 months, an RR of 1.03 for late‐stage disease risk at 3 months, an RR from 1.11 to 1.12 at 12 months, and an estimated decrement of 2.0% to 2.7% in LYG with a 3‐month interval to diagnostic testing …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The PROSPR multimodel study used 2 separate CRC modeling strategies side by side. That study reported an RR from 1.01 to 1.02 for lifetime disease risk at 3 months (compared with immediate diagnosis), an RR of 1.05 at 12 months, an RR of 1.03 for late‐stage disease risk at 3 months, an RR from 1.11 to 1.12 at 12 months, and an estimated decrement of 2.0% to 2.7% in LYG with a 3‐month interval to diagnostic testing …”
Section: Resultsmentioning
confidence: 95%
“…That study suggested no difference in the lifetime risk of breast cancer for wait times of 90 days to 1 year, but the relative risk (RR) for late‐stage disease was 1.08 at 90 days and 1.26 by 1 year. The modeling yielded a 17.3% decrement in estimated life‐years gained (LYG) when diagnostic testing occurred at 90 days …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because mammography is not 100% specific and can only identify suspicious lesions, all abnormal mammogram results require either subsequent imaging or biopsy until the abnormality is defined as either cancer or benign . This additional evaluation must be done in a timely manner in order to avoid delays in cancer diagnosis and to have the potential to achieve the benefits of screening …”
Section: Introductionmentioning
confidence: 99%
“…While there is no definitive definition of the length of time between an abnormal mammogram and resolution that constitutes a delay, there is evidence that more than 3 months between presentation and treatment initiation can lead to more advanced cancer at diagnosis . Additionally, a recent simulation study reported that, with each additional 3‐month delay between an abnormal mammogram and subsequent diagnostic testing, the distribution of breast cancers shifted toward a higher stage . Delays in resolution of abnormal mammogram results can cause women psychological distress, including anxiety and depression .…”
Section: Introductionmentioning
confidence: 99%